Optimal Regimens and Clinical Breakpoint of Avilamycin Against Clostridium perfringens in Swine Based on PK-PD Study - Huang, Anxiong; Luo, Xun; Xu, Zihui; Huang, Lingli; Wang, Xu; Xie, Shuyu; Pan, Yuanhu; Fang, Shiwei; Liu, Zhenli; Yuan, Zonghui; Hao, Haihong (Frontiers in Pharmacology, 2022)
Clostridium perfringens causes significant morbidity and mortality in swine worldwide. Avilamycin showed no cross resistance and good activity for treatment of C. perfringens. The aim of this study was to formulate optimal regimens of avilamycin treatment for C. perfringens infection based on the clinical breakpoint (CBP). The wild-type cutoff value (COWT) was defined as 0.25 μg/ml, which was developed based on the minimum inhibitory concentration (MIC) distributions of 120 C. perfringens isolates and calculated using ECOFFinder. Pharmacokinetics–pharmacodynamics (PK-PD) of avilamycin in ileal content were analyzed based on the high-performance liquid chromatography method and WinNonlin software to set up the target of PK/PD index (AUC0–24h/MIC)ex based on sigmoid Emax modeling. The PK parameters of AUC0–24h, Cmax, and Tmax in the intestinal tract were 428.62 ± 14.23 h μg/mL, 146.30 ± 13.41 μg/ml,, and 4 h, respectively. The target of (AUC0–24h/MIC)ex for bactericidal activity in intestinal content was 36.15 h. The PK-PD cutoff value (COPD) was defined as 8 μg/ml and calculated by Monte Carlo simulation. The dose regimen designed from the PK-PD study was 5.2 mg/kg mixed feeding and administrated for the treatment of C. perfringens infection. Five respective strains with different MICs were selected as the infection pathogens, and the clinical cutoff value was defined as 0.125 μg/ml based on the relationship between MIC and the possibility of cure (POC) following nonlinear regression analysis, CART, and “Window” approach. The CBP was set to be 0.25 μg/ml and selected by the integrated decision tree recommended by the Clinical Laboratory of Standard Institute. The formulation of the optimal regimens and CBP is good for clinical treatment and to control drug resistance.